2011
DOI: 10.1007/s12035-011-8178-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Profile of Antimaniac Effects of Histone Deacetylases Inhibitors

Abstract: An increasing number of studies have evaluated the potential therapeutic relevance of histone deacetylases (HDAC) inhibitors in mood disorder including bipolar disorder (BD). It has been suggested that the anterior limbic, which controls impulsivity and psychosis, is dysfunctional in BD. The present studies aims to evaluate the effects of microinjection of HDAC inhibitors in the ventricle, amygdala, striatum, prefrontal, and hippocampus on m-amphetamine-induced manic-like behavior in rats. Rats were given a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
2
32
2
Order By: Relevance
“…38 Therefore, the finding that AMPH-induced hyperlocomotion is partially blocked by SB treatment, as well as by Li and VPT treatment, suggests that SB may have mood-stabilizing properties. 18,29 Based on this pre-established relevance of the AMPH treatment as a valid animal model of mania, we are able to suggest that the results found in our experiments can be of relevance for human patients with BD. Nevertheless, clear extrapolations to the human condition regarding the doses of the tested drugs are less likely to be made, mostly due to differences in the metabolism of rats and humans and, therefore, in the kinetics of the drugs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…38 Therefore, the finding that AMPH-induced hyperlocomotion is partially blocked by SB treatment, as well as by Li and VPT treatment, suggests that SB may have mood-stabilizing properties. 18,29 Based on this pre-established relevance of the AMPH treatment as a valid animal model of mania, we are able to suggest that the results found in our experiments can be of relevance for human patients with BD. Nevertheless, clear extrapolations to the human condition regarding the doses of the tested drugs are less likely to be made, mostly due to differences in the metabolism of rats and humans and, therefore, in the kinetics of the drugs.…”
Section: Discussionmentioning
confidence: 52%
“…More recently, Arent et al showed different effects of SB treatment in specific brain regions, suggesting that the antimanic effects of SB and of VPT are related to the amygdala, striatum, and, of special interest here, to the PFC, although not to the hippocampus. 29 More studies are warranted to clarify the effects of these HDAC inhibitors in different brain regions. Of note, the lack of between-group differences in HDAC activity in PBMCs in our sample suggests that the modulation of HDAC activity by the tested drugs is mainly central and cannot be observed in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…or saline [17]. Eighteen hours after induction, all animals received ceftriaxone (100-mg/kg body weight given s.c./7 days) [18].…”
Section: Treatmentmentioning
confidence: 99%
“…It has been shown that VPA modulates the epigenetic programming by inhibiting histone deacetylases (HDAC) (Machado-Vieira et al, 2011). Recent preclinical studies from our research group showed that treatment with sodium butyrate (SB), an inhibitor of histone deacetylase like VPA, was able to reverse the manic-like behavior induced by amphetamine in rodents (Arent et al, 2011;Resende et al, 2013;Steckert et al, 2013;Valvassori et al, 2013).…”
Section: Introductionmentioning
confidence: 99%